Nicotinic receptor agonists decrease L-dopa-induced dyskinesias most effectively in partially lesioned parkinsonian rats - Huang, Luping Z. (2011)
L-dopa therapy for Parkinson's disease leads to dyskinesias or abnormal involuntary movement (AIMs) for which there are few treatment options. Our previous data showed that nicotine administration reduced L-dopa-induced AIMs in parkinsonian monkeys and rats. To further understand how nicotine mediates its antidyskinetic action, we investigated the effect of nicotinic receptor (nAChR) agonists in unilateral 6-OHDA-lesioned rats with varying striatal damage. We first tested the drugs in L-dopa-treated rats with a near-complete striatal dopamine lesion (>99%), the standard rodent dyskinesia model. Varenicline, an agonist that interacts with multiple nAChRs, did not significantly reduce L-dopa-induced AIMs, while 5-iodo-A-85380 (A-85380), which acts selectively at α4β2* and α6β2* subtypes, reduced AIMs by 20%. By contrast, both varenicline and A-85380 reduced L-dopa-induced AIMs by 40–50% in rats with a partial striatal dopamine lesion. Neither drug worsened the antiparkinsonian action of L-dopa. The results show that selective nicotinic agonists reduce dyskinesias, and that they are optimally effective in animals with partial striatal dopamine damage. These findings suggest that presynaptic dopamine terminal α4β2* and α6β2* nAChRs are critical for nicotine’s antidyskinetic action. The current data have important implications for the use of nicotinic receptor-directed drugs for L-dopa-induced dyskinesias, a debilitating motor complication of dopamine replacement therapy for Parkinson’s disease.